The Strength Analysis of a Bus Superstructure Based on the Accuracy Improvement of T-Junction Flexible Joint Stiffness - Rooppakhun, Supakit; Wichairahad, Jakkree (International Journal of Engineering and Technology, 2018)
The strength analysis of bus superstructure was extremely important that the manufacturer must take into account, especially in the maximum stress analysis as well as the construction stiffness. In this study, the finite element (FE) model of an intercity bus superstructure consisted of chassis frame and body structure has been analyzed based on the improved beam joint considerations. The accuracy improvement of beam type element model was performed using the equivalent joint stiffness of T-junction beam modeling, and then compared with shell and volume elements. According to the improved T-junction FE model, the flexible joint stiffness consideration has been obtained, in which the behavioral error was reduced to less than 6%. The FE model of bus superstructure with improved beam joint was then compared to the rigid joint condition in bending, torsion, longitudinal and lateral load cases. The numerical results revealed that magnitude of maximum stress in the improved beam joint model displayed increasing of 11.53 %, 14.11 %, and 18.45 % in torsion, longitudinal and lateral load cases, respectively. However, the maximum stresses reduced in a case of bending with value of 5.72 %. In addition, the value of construction stiffness of improved beam joint model exhibited lower than the rigid beam joint as 44.85%, and 10.68% in the bending and torsion load case, respectively. To improve the accuracy of computer simulation, it will be beneficial to the passenger and the bus structure design and improvement procedure.Â